Identification of immunostimulatory antigens in Group A Streptococcus –derived vesicles - Meztlli O. Gaytán; Rebecca S. Dookie; Sayoni Chakraborty; Anandi Narayana Moorthy; Stefan Kreida; Anna Norrby-Teglund; John Boss; Max Heurgren; Staffan Normark; Birgitta Henriques-Normark (Proceedings of the National Academy of Sciences, 2026)
An effective vaccine against Streptococcus pyogenes (Group A Streptococcus , GAS) is urgently needed. Bacteria-derived extracellular vesicles (EVs) are emerging as promising vaccine platforms. In this study, we evaluated the immunostimulatory properties of GAS-derived EVs when administered intranasally in mice. Immunization induced a strong humoral response, including pathogen-specific immunoglobulin G (IgG) and immunoglobulin A (IgA) antibodies. Additionally, we observed local and systemic T cell responses, specifically a robust Th17 response along with a modest but statistically significant Th1 response. Through immunoprecipitation coupled with mass spectrometry and western blotting, we identified seven immunogenic proteins, including the lipoproteins MtsA, BMP, PrsA1, PrsA2, MetQ, MalX, and the glutamine transporter GlnP. These antigens were recognized by human sera from both healthy individuals and patients with necrotizing soft tissue infection. Finally, we demonstrate that these antigens stimulate production and secretion of IL-17A by lung cells and splenocytes and that they are highly conserved across diverse GAS M-types, highlighting their potential as broadly protective vaccine candidates.